A mechanism of the auroral substorm expansion onset: electric discharge in the double layer - Song, Yan; Lysak, R. L. (Frontiers in Astronomy and Space Sciences, 2023)
Magnetospheric substorms often occur when a significant amount of energy from the solar wind is deposited and stored in the magnetotail during the growth phase and release explosively in the expansion phase, which accelerates charged particles causing the rapid auroral intensification. A physical mechanism is needed to release the energy explosively. The formation of double layers is a likely mechanism for the energy release and the acceleration of particles and triggers the onset of the expansion phase. We suggest that the localized parallel electric field that forms the double layer results from the displacement current complying with Ampere's law for the dynamic case. The double layers are embedded in low density cavities surrounded by enhanced magnetic stresses. Positive feedback in the electric field generation may cause rapid release of the accumulated energy. The Poynting flux carried by Alfven waves continuously supplies the energy to maintain strong electric fields during the rapid development of auroral substorms.